Metastatic hormone-sensitive prostate cancer - outcomes of docetaxel plus androgen-deprivation therapy as first line treatment in a portuguese center - Piedade, Ana Rita Santos (2022)
Trabalho Final do Mestrado Integrado em Medicina apresentado à Faculdade de Medicina